Structural study of the interaction of vanadate with the ligand 1,2-dimethyl-3-hydroxy-4-pyridinone (Hdmpp) in aqueous solution - Castro, M. M. C. A. (2000)
The interaction of vanadate with the ligand 1,2-dimethyl-3-hydroxy-4-pyridinone (Hdmpp) was studied in aqueous solution using a combination of multinuclear NMR and EPR spectroscopies, as well as potentiometry and cyclic voltammetry. The different species in solution were identified and characterized, and their pKa values and stability constants determined. The vanadium complexes formed in solution are strongly dependent on media composition (ionic strength, presence of buffer), pH and metal-to-ligand ratio (M:L). Two major species -- V(V)/dmpp and V(V)/(dmpp)2 -- are formed in a 140 mM NaCl solution within the pH range 4.5 to 9.0, when M:L=1:2. In the presence of excess ligand (M:L<=1:5), only the 1:2 complex is present, and at pH<4 paramagnetic species are detected by EPR in solution, thus indicating a reducing capacity of the ligand. Cyclic voltammetry shows that redox processes in solution are not just electron transfer, but are accompanied by chemical reactions. The pKa values and stability constants were determined both by 51V NMR spectroscopy and potentiometry. The present results have a particular interest in the understanding of the aqueous solution chemistry in aerobic conditions of bis(1,2-dimethyl-3-hydroxy-4-pyridinonato) oxovanadium(IV) complex, VO(dmpp)2, a vanadium compound with potential insulin-mimetic properties.